PENGARUH PENGENDALIAN INTERNAL DAN TUNJANGAN TERHADAP KINERJA PEGAWAI PADA PENGADILAN TATA USAHA NEGARA BANDAR LAMPUNG - Yil Mustopa; Maidiana Astuti H; Dewi Sukmasari (Faculty of Economics and Business, 2022)
This study aims to analyze the effect of internal control and benefits on employee performance at PTUN. The sample was determined by saturated sampling technique and obtained 42 PTUN employees. This research is a type of quantitative research. Data analysis methods used in this study include reliability test, validity test, R2 determination test, multiple regression analysis test, f test (simultaneous), t test (partial). The results of the study indicate that the internal control variables and allowances have a positive and significant effect on employee performance at the Bandar Lampung State Administrative Court as seen from the significant value of 0.000 0.05. The results of this study are expected that the internal control variables can be used as guidelines by management in improving employee performance. Keywords: internal control, benefits and employee performance.